Description of brachial plexus of sloth (Bradypus variegatus) - Silvia F. Alcântara; Marleyne J.A.L. Amorim; Priscilla V. Albuquerque; Emanuela P. Mesquita; Maria Eduarda L.C. Miranda; Gilcifran P. Andrade; Nathalia E.O. Nascimento; Júlio C.S. Nascimento (Pesquisa Veterinária Brasileira, 2020)
ABSTRACT: The species Bradypus variegatus is known as the common sloth, an endemic mammal from neotropical regions, which has been suffering from devastating anthropogenic activities. Our study aimed to describe the brachial plexus of B. variegates, regarding the origin and distribution of nerves, through the sampling of 10 adult females. Analyses were carried out at the Anatomy Section, “Departamento de Morfologia e Fisiologia Animal”, “Universidade Federal Rural de Pernambuco”, under license no. 034/2015 of the Ethics Committee on the Use of Animals. The results determined that the brachial plexus of the common sloth starts from the fifth cervical spine segment until the second thoracic segment. This area contains the long and suprascapular thoracic nerves, which originate immediately from the medullary segment 5 and 6, respectively, and from the pectoral, subscapular, axillary, radial, musculocutaneous, medial, forearm and ulnar medial cutaneous nerves, arising from a trunk comprised of cervical spine nerves (C) 7, C8, C9, and thoracic (T) 1 and T2. Regarding other wild and domestic animals, different suggestions were observed about the origin of the plexus in B. variegatus, however, the constituent nerves and their innervation areas did not demonstrate any discrepancies.